(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Indian Prose in English flourishes and blossoms in both consistency and quantity by leaps and bounds. Indian English litterateurs have been making their appearance world-wide over the last few decades. The achievement of the Indian English Novel in literature is exceptional. Indian novelists such as R. Contemporary Indian culture was envisaged by K. Narayan, Mulk Raj Anand and Raja Rao. In addition to these novelists, numerous facets of Indian life and culture were also discussed by Arundhati Roy, Kiran Desai, Aravind Adiga, Chetan Bhagat, etc. A bit different from all these authors is Chetan Bhagat. He not only speaks about the traditional social life in India, but also presents the issues in youth. Bhagat shows how young people attempt to address their issues by his young characters. Via his books, he reveals the promise of juveniles. The young generation are inspired by Bhagat. Indian youth become completely optimistic in facing unforeseen challenges that arise in their lives after reading Bhagat ’s novels. An attempt has been made in the current research paper to figure out the various themes in Chetan Bhagat ’s chosen novels. The present thesis attempts to address the numerous main topics such as college existence, faulty school infrastructure, cultural tension and existence ideology, educational corruption, human relationships and national honesty. It also discusses some minor subjects, such as identity quest, hope, inter-caste marriage, passive politics, and the battle for life.